Surface Brillouin scattering studies of high-temperature elasticity - Stoddart, Paul Randall (University of the Witwatersrand, Johannesburg, 1999)
A novel technique has been developed for studying the elastic proper ties of opaque solids at high temperatures. The method is based on surface Brillouin scattering (SBS) and has the advantages of being contact-free and non-destructive. The elastic constants can be extracted from SBS measurements of the directional dependence of the surface wave velocities. An optical furnace was designed to provide the special scattering geometry required for these measurements. The technique has been evaluated on silicon and a single-crystal nickel-based superalloy, with measurements up to 800°C and 200°C respectively. Above these temperatures, measurements were precluded by a marked deterioration in the surface quality. The elastic constants for silicon compare favourably with the established ultrasonic values, particularly in terms of the changes as a function of temperature. Additional measurement were performed on silicon at temperatures up to 900°C in order to examine the well-known central mode feature. These results shed light on a major outstanding problem in SBS, because they reveal the presence of a second quasielastic mode that may be associated with scattering from diffusive excitations. Further measurements at high and low temperatures are proposed to confirm the mechanism. Silicon was also used as a test system to clarify certain aspects of the theory and practice of SBS that have not been properly dealt with before, such as the effects of surface anisotropy and of the extended collection aperture. This indicates that SBS provides effective elastic constants for the outer 300 nm of the sample surface and thus may be influenced by surface damage and surface contamination. In the case of the superalloy, the difficulties encountered in gathering data at higher temperatures suggests that modifications to the furnace arrangement are required. The larger relative error in the velocities also created problems in the extraction of the elastic constants. This difficulty was satisfactorily overcome by using the longitudinal threshold in the Lamb shoulder to fix the value of c₁₁. Although the work described here has been limited to temperatures below 900°C, it is clear that SBS provides a powerful method for probing the elastic properties of opaque solids at elevated temperatures.
A thesis submitted in fulfilment of the requirements for the degree of Doc tor of Philosophy, to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 1999.
Keywords: Surface Brillouin scattering (SBS); Surface wave velocities.; Silicon; Single-crystal nickel-based superalloy; Elastic properties; Opaque solids; UCTD; N/A